137Cs transport in crushed granitic rock: The effect of bentonite colloids. (September 2018) - Kolomá, Kateřina; Červinka, Radek; Hanusová, Irena
Abstract: The paper focuses on the study of caesium transport through crushed granite in the presence of bentonite colloids in a dynamic column arrangement with the continuous input of the liquid phase. The aim of the experiments was to investigate the effect of the presence of bentonite colloids on the behaviour of caesium in granitic rock. The behaviour of the tracer was studied under aerobic conditions applying a constant tracer concentration (activity) and constant flow rate. Defined volumes of the liquid phase were sampled periodically at the outlet of the column for the measurement of tracer concentrations (activity). Transport was described by means of breakthrough curves. The stepwise approach included the following steps: 1) the non sorbing tracer 3 H was used to evaluate the hydrodynamic properties of the column; 2) the conducting of a column experiment with bentonite colloids in deionised water; 3) the migration of 137 Cs in two liquid phases (deionised and synthetic granitic water); 4) the study of the transport of the radiocolloid suspension in deionised water. The results revealed the completely different behaviour of the bentonite colloids and the caesium in the granitic column and the effect of colloid particles on caesium sorption on granite. The bentonite colloids behaved as conservative non-sorbing tracers whereas, conversely, caesium sorbed strongly on the granitic material. It was determined that the behaviour of the caesium in the granitic rock was influenced by the strong sorption of caesium with respect to the bentonite colloids. A minor part of the caesium irreversibly sorbed on the bentonite colloids and passed through the granite immediately together with the bentonite colloids, and a major part of the caesium was desorbed from the bentonite colloids and was retained in the granite. Highlights: The retention of caesium on granite is caused principally by the presence of mafic minerals and plagioclase. The composition of the liquid phase is a significant parameter with respect to influencing caesium sorption on granite. The bentonite colloid particles partially play the minor role of radionuclide carriers.